Protein transport in organelles: Protein transport into and across the thylakoid membrane. - Aldridge, C; Cain, P; Robinson, C (2009)
The chloroplast thylakoid is the most abundant membrane system in nature, and is responsible for the critical processes of light capture, electron transport and photophosphorylation. Most of the resident proteins are imported from the cytosol and then transported into or across the thylakoid membrane. This minireview describes the multitude of pathways used for these proteins. We discuss the huge differences in the mechanisms involved in the secretory and twin-arginine translocase pathways used for the transport of proteins into the lumen, with an emphasis on the differing substrate conformations and energy requirements. We also discuss the rationale for the use of two different systems for membrane protein insertion: the signal recognition particle pathway and the so-called spontaneous pathway. The recent crystallization of a key chloroplast signal recognition particle component provides new insights into this rather unique form of signal recognition particle.